Low-cost biochar derived from corncob as oxygen reduction catalyst in air cathode microbial fuel cells. (1st September 2018) - Li, Meng; Zhang, Hongguo; Xiao, Tangfu; Wang, Shengdan; Zhang, Bopeng; Chen, Diyun; Su, Minhua; Tang, Jinfeng
Abstract: Low-cost biochar derived from corncob was prepared by a facile pyrolysis method at controlled temperatures (250–750 °C) and the biochar was employed as oxygen reduction reaction (ORR) catalyst in air cathode microbial fuel cells (MFCs). The obtained biochar at 650 °C (CC-650) showed an excellent electrochemical active area up to 655.89 m 2  g −1, and various forms of nitrogen were introduced to the carbon molecular skeleton successfully. The electrochemical measurements indicated that the CC-650 with the highest contents of graphitic and pyridinic nitrogen can accelerate the electron transfer to participate in ORR by a four-electron pathway. In MFCs tests, the maximum output voltage and power density with CC-650 cathode was 0.221 V and 458.85 mW m −3 respectively, which was significantly higher than those of the other biochar. Our results demonstrated a potential route based on sustainable and economical biochar as promising oxygen reduction catalyst for MFCs. Graphical abstract: Image 1 Highlights: A facile and low-cost method to synthesize the biochar. The optimal electrocatalytic activity was achieved with the sample synthesized at 650 °C. The biochar (CC-650) can accelerate the electron transfer. The biochar was a potential oxygen reduction catalyst for MFCs.